2009
DOI: 10.1080/14616690902764815
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the Same Fate

Abstract: Peer support has become a growing source of consolation for individuals in contemporary social life. This article examines the social bond between selves and their fellow sufferers 'sharing the same fate' in support groups and personal networks. Analyzed fateful conditions include serious illness, premature loss of a spouse through death or abandonment, infertility and family disruptions. The results show that selves colonized by agonizing life experiences confront social isolation and turn to their fellow suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…Peer support can offer a unique type of relationship that provides generalization of experience and social validation, and promotes feelings of empowerment [7]. In general, peer support is associated with decreased loneliness and feelings of difference, as well as enhanced social competence, social acceptance, and increased acceptance of chronic conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Peer support can offer a unique type of relationship that provides generalization of experience and social validation, and promotes feelings of empowerment [7]. In general, peer support is associated with decreased loneliness and feelings of difference, as well as enhanced social competence, social acceptance, and increased acceptance of chronic conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such a processual focus on a range of relationships is difficult to capture by focusing solely on belonging. In line with Ketokivi's (2009) scholarship on peer support and suffering selves, we consider the affective pull of biosocial similarity in moments of suffering and the kinds of social bonds that bind fellow sufferers, as well as how these are negotiated according to dis/ similar diagnosis. Unlike social bonds with family or friends, the bond between fellow sufferers Ketokivi (2009) points out, is 'a voluntary and openly individualistic bond which one can enter into and exit from at any time, based on the needs of the self' (p. 90).…”
Section: Conceptualising Biosocial Belonging (And Exclusion) Through ...mentioning
confidence: 99%
“…In line with Ketokivi's (2009) scholarship on peer support and suffering selves, we consider the affective pull of biosocial similarity in moments of suffering and the kinds of social bonds that bind fellow sufferers, as well as how these are negotiated according to dis/ similar diagnosis. Unlike social bonds with family or friends, the bond between fellow sufferers Ketokivi (2009) points out, is 'a voluntary and openly individualistic bond which one can enter into and exit from at any time, based on the needs of the self' (p. 90). Building on this work, here, we examine the social bonds of women with metastatic breast cancer and others within their social worlds, paying attention to how experiences of (in)visibility, (in)authenticity and (in)validation variously constitute and/or erode social bonds.…”
Section: Conceptualising Biosocial Belonging (And Exclusion) Through ...mentioning
confidence: 99%
“…Before the COVID‐19 pandemic, these groups provided members with a context for social interaction in a physical space through a range of activities built around a programme of peer support (Dorning et al, 2016 ). Group‐based peer support, founded on shared health experiences, is associated with reductions in feelings of isolation and can promote feelings of empowerment in people living with a range of health conditions, including stroke survivors (Ketokivi, 2009 ; Tamplin et al, 2013 ). An earlier evaluation of these SA peer support groups before the pandemic showed that group members feel positive about being part of a group and report that their confidence, social networks, health and well‐being benefitted from their participation (Dorning et al, 2016 ).…”
Section: The Supportive Effects Of Group Membershipmentioning
confidence: 99%